Catastrophic Geological Event Illuminates Egyptian Kings List Anno Mundi Reference - Giannini, Judith (European Journal of Applied Sciences, 2021)
The preponderance of catastrophe myths in ancient cultures around the world indicates the importance of contemplating the ancient beginnings. This paper considers the legendary Egyptian beginning of the world event, Anno Mundi, to which Eratosthenes referenced the reign of the first king of the Unification, Menes. Menes’ identity is still in question, and the nature of the event is left undefined. First, the dates for the possible candidates for the person Menes as a starting point to locate AM in time are considered. Next, possible event types that might qualify as world-defining events are considered. Finally, it is concluded that a geological event (an unrelenting series of closely spaced eruptions on Mount Erciyes in Anatolia) in 8200 BP is consistent with the expected date for the Anno Mundi, and the reign date for King Scorpion(I) who is proposed as the most likely Menes based on all of the considerations. It is believed the identified date and Menes candidate provide a plausible explanation for the otherwise unsubstantiated legendary event.